Spatial distribution of snow cover and temperature in the upper layer of a polythermal glacier - T. V. Vshivtseva; R. A. Chernov (Лëд и снег, 2017)
The thermal regime of the upper layers of any glacier largely determines the thermal structure of its entire thickness. Its formation is influenced by both, external and internal factors and the most important one among them is the snow cover. Playing the role of a heat insulator in winter and preventing the ablation of ice in summer, the snow cover mainly determines the winter storage of cold in the ice, and the temperature at the bottom of the active layer. In 2011–2015, the close relationship between the thickness of snow and temperatures in the upper horizons of ice had been found in the course of researches carried out on the glacier East Grønfjord (Svalbard). Comparison of snow measurement survey data, obtained for different years of the period under investigation, did show that, in every year, the maximum snow accumulation took place within the left branch of the glacier, while the snow thickness within the right branch was comparable to that on the glacier tongue. Thus, observed differences in the snow accumulation cause differences in the temperature structure of the upper layers of the ice. Inter-annual variations of the snow cover thickness indicate that conditions of freezing remain stable overthe greater part of the glacier. Only in the upper reaches of the glacier left branch the great snow accumulation creates conditions unfavorable for freezing. This part of the glacier is more inert to changes in climate, and due to that a wide area of warm ice still remains at the bottom of the glacier.